Deploying the Total Operating Characteristic to Assess the Relationship between Land Cover Change and Land Surface Temperature in Abeokuta South, Nigeria - Thomas Mumuni Bilintoh; Juwon Isaac Ishola; Adeline Akansobe (Land, 2022)
Urbanization affects land cover and a region’s prevailing land surface temperature (LST). As a result, understanding the effects of urbanization on LST and land cover change is critical for effectively planning, managing, and monitoring urban development and undesired LST change. This paper, therefore, examines the relationship between the change in four land cover categories and LST during 1987–2004 and 2004–2021. Our approach uses the Total Operating Characteristic (TOC) to study the relationship between LST change and the losses and gains in four land cover categories: infrastructure, vegetation, water, and bare land in Abeokuta South, Nigeria. We derived the land cover and LST dataset from satellite imagery at time points 1987, 2004, and 2021. Our results show that most of the vegetation in the study area transitions to bare land and infrastructure during both time intervals, while most of the bare areas transition to infrastructure and vegetation. Furthermore, the TOC analysis shows vegetation loss, gain in infrastructure, and bare land occurs more intensively at segments between increased thresholds of LST values during both time intervals. Conversely, vegetation gain, infrastructure, and bare land loss occur more intensely at segments between decreased LST values. The methods discussed herein can reveal important insights and stimulate the needed conversation concerning the effective planning, managing, and monitoring of urban development and undesired LST change.